2021
DOI: 10.1002/dmrr.3486
|View full text |Cite
|
Sign up to set email alerts
|

Screening for monogenic subtypes of gestational diabetes in a high prevalence island population – A whole exome sequencing study

Abstract: Aims The reported frequency of monogenic defects of beta cell function in gestational diabetes (GDM) varies extensively. This study aimed to evaluate the frequency and molecular spectrum of variants in genes associated with monogenic/atypical diabetes in non‐obese females of Maltese ethnicity with GDM. Methods 50 non‐obese females who met the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria for diagnosis of GDM and with a first‐degree relative with non‐autoimmune diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…To our knowledge, WES has been widely used in clinical and genomic research; however, only one study has used this method to identify genetic variants in GDM cases. A recent study by Nikolai Paul et al screened 50 non-obese GDM Maltese women, and identified three pathogenic variants, rs201815564, rs37046485, and rs766191969, in the ABCC8 , GCK , and HNF1A genes, respectively [ 97 ]. Additionally, subjects with these variants reported interrupted fasting glucose levels several times [ 97 ].…”
Section: Genomic Approaches Used In Understanding Gestational Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, WES has been widely used in clinical and genomic research; however, only one study has used this method to identify genetic variants in GDM cases. A recent study by Nikolai Paul et al screened 50 non-obese GDM Maltese women, and identified three pathogenic variants, rs201815564, rs37046485, and rs766191969, in the ABCC8 , GCK , and HNF1A genes, respectively [ 97 ]. Additionally, subjects with these variants reported interrupted fasting glucose levels several times [ 97 ].…”
Section: Genomic Approaches Used In Understanding Gestational Diabetesmentioning
confidence: 99%
“…A recent study by Nikolai Paul et al screened 50 non-obese GDM Maltese women, and identified three pathogenic variants, rs201815564, rs37046485, and rs766191969, in the ABCC8 , GCK , and HNF1A genes, respectively [ 97 ]. Additionally, subjects with these variants reported interrupted fasting glucose levels several times [ 97 ]. Nevertheless, replication of these studies is needed considering the limited number of subjects, the ethnic heterogeneity of the Maltese population, and the possibility of variants in intronic regions not covered by WES [ 97 ].…”
Section: Genomic Approaches Used In Understanding Gestational Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coincidentally in 2019, Malta had the highest recorded obesity rates, in both sexes, amongst the EU countries. Obesity is one of the predisposing factors of diabetes and this together with various genetic mutations identified in the Maltese population contribute to the high prevalence of diabetes in Malta (Eurostat, 2021; Cuschieri et al., 2016 ; Pace et al., 2019 , 2021 ). As diabetic patients are at risk of ischaemia, peripheral neuropathy and an impaired immunity, 12–25% are at a high risk of developing diabetic foot ulcers (DFUs).…”
Section: Introductionmentioning
confidence: 99%